Insulin affects sperm capacity in pig through nitric oxide - Aquila, Saveria (Nature Publishing Group, 2013)
Insulin (Ins) has recently been demonstrated to have the ability to induce the capacitation process in pig spermatozoa. In various mammalian species, capacitation has been linked to the nitric oxide (NO) signalling; therefore, this study investigated NO production in Ins-treated pig spermatozoa by fluorescence-activated cell sorting. For the same samples, sperm capacitation was evaluated by chlortetracycline staining, protein tyrosine phosphorylation pattern and acrosomal status. A significant increase of the intrasperm NO level and the activation of three capacitation indices were detected in response to Ins treatment. Conversely, sperm preincubation with an NO synthase inhibitor (N-nitro-L-arginine methyl ester) or with the anti-Ins receptor β (IRβ) antibody reversed all of the Ins-related effects. These results suggest that Ins has the capacity to enhance intracellular NO concentrations in pig spermatozoa and indicate a possible NO implication upon Ins promotion of capacitation.